2020
DOI: 10.1523/jneurosci.2471-19.2020
|View full text |Cite
|
Sign up to set email alerts
|

Nestin Selectively Facilitates the Phosphorylation of the Lissencephaly-Linked Protein Doublecortin (DCX) by cdk5/p35 to Regulate Growth Cone Morphology and Sema3a Sensitivity in Developing Neurons

Abstract: Nestin, an intermediate filament protein widely used as a marker of neural progenitors, was recently found to be expressed transiently in developing cortical neurons in culture and in developing mouse cortex. In young cortical cultures, nestin regulates axonal growth cone morphology. In addition, nestin, which is known to bind the neuronal cdk5/p35 kinase, affects responses to axon guidance cues upstream of cdk5, specifically, to Sema3a. Changes in growth cone morphology require rearrangements of cytoskeletal … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 87 publications
(130 reference statements)
0
13
0
Order By: Relevance
“…5 D, ). Plxna2 , a gene involved in semaphorin/plexin signaling for axon guidance ( Rohm et al, 2000 ; Mitsogiannis et al, 2017 ), and Dcx , a gene that in addition to its function in neuronal migration has been connected to neuronal morphogenesis and axon guidance ( Deuel et al, 2006 ; Pilz et al, 1998 ; Yap et al, 2016 ; Bott et al, 2020 ), were selected for further investigation. Evolutionarily conserved regions (ECRs) upstream of or at the promotor containing conserved binding sites for TCF4 and SOX11 ( …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…5 D, ). Plxna2 , a gene involved in semaphorin/plexin signaling for axon guidance ( Rohm et al, 2000 ; Mitsogiannis et al, 2017 ), and Dcx , a gene that in addition to its function in neuronal migration has been connected to neuronal morphogenesis and axon guidance ( Deuel et al, 2006 ; Pilz et al, 1998 ; Yap et al, 2016 ; Bott et al, 2020 ), were selected for further investigation. Evolutionarily conserved regions (ECRs) upstream of or at the promotor containing conserved binding sites for TCF4 and SOX11 ( …”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, we present in vitro biochemical evidence for several of the predicted interactions and provide in vivo biochemical and genetic evidence for the cooperativity of TCF4 with the non-bHLH transcription factor SOX11 in the generation of the commissural system. We identified two potential common target genes of TCF4 and SOX11, Dcx and Plxna2 , which have been shown to play important roles in axonal development and axon guidance ( Rohm et al, 2000 ; Mitsogiannis et al, 2017 ; Deuel et al, 2006 ; Pilz et al, 1998 ; Yap et al, 2016 ; Bott et al, 2020 ) and are likely candidates to contribute to the observed dysgenesis of the forebrain commissures in Tcf4 KO mice. These two genes are, however, only two examples out of a larger network of factors involved in commissural formation that are dysregulated as a result of changes in GRN activities caused by the loss of TCF4B.…”
Section: Discussionmentioning
confidence: 99%
“…They have differential expression patterns that influence the response, for instance, the atypical intermediate filament nestin, which is expressed in neuronal progenitors and newborn neurons, localizes mainly to the distal area of growing axons in embryonic, but not in adult neurons [ 67 ]. Neurons expressing nestin are more sensitive to Sema3A than the ones that do not express it [ 67 ], and this effect is dependent on Doublecortin (DCX) [ 68 ]. Nestin binds DCX and the cdk5 kinase activator p53, facilitating DCX phosphorylation by cdk5, a kinase that acts downstream of Sema3A [ 68 ].…”
Section: Guidance Cues In Concertmentioning
confidence: 99%
“…Neurons expressing nestin are more sensitive to Sema3A than the ones that do not express it [ 67 ], and this effect is dependent on Doublecortin (DCX) [ 68 ]. Nestin binds DCX and the cdk5 kinase activator p53, facilitating DCX phosphorylation by cdk5, a kinase that acts downstream of Sema3A [ 68 ]. Interestingly, studies in Xenopus laevis , comparing the transcriptomic response after spinal cord injury (SCI) in R versus NR stages, showed a differential increase in nestin transcripts in NR-stages, while no changes in R-stages, at 6 days post-injury (dpi) [ 69 , 70 ].…”
Section: Guidance Cues In Concertmentioning
confidence: 99%
“…More recent work has elucidated that cdk5/p35 is the mechanism through which the neuronal intermediate filament protein Nestin facilitates phosphorylation of the critical neuronal migration factor doublecortin (DCX), which is also linked to lissencephaly. This Nestin-driven phosphorylation of DCX, thought cdk5/p35, affects both growth cone morphology and sensitivity to the axonal chemorepellent Sema3a ( Bott et al, 2020 ). Thus, while mPTP is not directly implicated in these processes, the key roles of cdk5 during cortical development, particularly migration of newly differentiated neurons, suggests mPTP as an intriguing process worthy of further study as a potential mechanism further linking the two converging fields of corticogenesis and mitochondria.…”
Section: Implications and Open Questionsmentioning
confidence: 99%